Liver Dangers of Herbal Products: A Case Report of Ashwagandha-Induced Liver Injury - Marta Lubarska; Przemysław Hałasiński; Szymon Hryhorowicz; Dagmara Santabye Mahadea; Liliana Łykowska-Szuber; Piotr Eder; Agnieszka Dobrowolska; Iwona Krela-Kaźmierczak (International Journal of Environmental Research and Public Health, 2023)
In recent years, cases of liver damage caused by ashwagandha herbal supplements have been reported from different parts of the world (Japan, Iceland, India, and the USA). Here, we describe the clinical phenotype of suspected ashwagandha-induced liver injury and the potential causative mechanism. The patient was admitted to the hospital because of jaundice. In the interview, it was reported that he had been taking ashwagandha for a year. Laboratory results showed an increase in total bilirubin, alanine transaminase (ALT), aspartate transaminase (AST), (gamma-glutamyl transpherase (GGT), alkaline phosphatase (ALP), total cholesterol, triglycerides, and ferritin. Based on clinical symptoms and additional tests, the patient was diagnosed with acute hepatitis and referred to a facility with a higher reference rate to exclude drug-induced liver injury. An R-value was assessed, indicative of hepatocellular injury. The result of the 24 h urine collection exceeded the upper limit of normal for copper excretion in urine twice. The clinical condition improved after intensive pharmacological treatment and four plasmapheresis treatments. This case is another showing the hepatotoxic potential of ashwagandha to cause cholestatic liver damage mixed with severe jaundice. In view of several documented cases of liver damage caused by ashwagandha and the unknown metabolic molecular mechanisms of substances contained in it, attention should be paid to patients reporting the use of these products in the past and presenting symptoms of liver damage.